2019
DOI: 10.3748/wjg.v25.i19.2373
|View full text |Cite
|
Sign up to set email alerts
|

New antireflux plastic stent for patients with distal malignant biliary obstruction

Abstract: BACKGROUND Endoscopic biliary stenting is a well-established palliative treatment for patients with unresectable distal malignant biliary obstruction (MBO). However, the main problem with stent placement is the relatively short duration of stent patency. Although self-expanding metal stents (SEMSs) have a longer patency period than plastic stents (PSs), the higher costs limit the wide use of SEMSs. A PS with an antireflux valve is an attractive idea to prolong stent patency, but no ideal design fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In a subsequent clinical RCT involving 60 patients with distal MBO, the antireflux plastic stent provided 1.5‐fold prolonged patency time compared to a conventional plastic biliary stent (median patency times, 145 days vs. 101 days, respectively) 43 . However, inconsistent results were reported by subsequent trials investigating the same stent or other types of antireflux plastic stents 44–46 …”
Section: Antireflux Biliary Stents: a Developing Treatment Modalitymentioning
confidence: 99%
See 1 more Smart Citation
“…In a subsequent clinical RCT involving 60 patients with distal MBO, the antireflux plastic stent provided 1.5‐fold prolonged patency time compared to a conventional plastic biliary stent (median patency times, 145 days vs. 101 days, respectively) 43 . However, inconsistent results were reported by subsequent trials investigating the same stent or other types of antireflux plastic stents 44–46 …”
Section: Antireflux Biliary Stents: a Developing Treatment Modalitymentioning
confidence: 99%
“…43 However, inconsistent results were reported by subsequent trials investigating the same stent or other types of antireflux plastic stents. [44][45][46] According to the increasing popularity of SEMSs in the setting of nonresectable distal MBO, researchers were motivated to develop ARMSs for this indication. While the designs of antireflux valves in prior studies were heterogeneous, 47 ARMSs have been generally associated with lower risks of stent occlusion and non-occlusion cholangitis compared to conventional SEMSs.…”
Section: Antireflux Biliary Stents: a Developing Treatment Modalitymentioning
confidence: 99%
“…Plastic stent obstruction might occur due to sludge reflux pancreatitis. Recently, a novel plastic stent to prevent duodenal juice reflux has been developed [9]. This stent has a 1.5-cm-long antireflux valve made of silicone rubber material attached to the duodenal site.…”
Section: Endoscopic Approach For Mpd Stricture Using Plastic Stentmentioning
confidence: 99%
“…Efforts have been made towards the design of anti-reflux biliary stents for preventing duodenobiliary reflux after biliary stent implantation. Recently, some types of anti-reflux stents with different valves have been proposed, such as duckbilled ( Yuan et al, 2019 ), hemispheric ( Hu et al, 2011 ), funnel-shaped ( Morita et al, 2018 ), S-shaped ( Lee et al, 2013 ), nipple-shaped ( Hu et al, 2014 ), wine-glass-shaped ( Kim et al, 2013 ), and windsock-shaped valves ( Lee et al, 2016 ). It has been reported that implantation of anti-reflux biliary stents was safe and feasible, giving its higher technical success rate, longer stent patency, and no influence on the antegrade flow of bile ( Dua et al, 2007 ; Hu et al, 2011 ; Renno et al, 2019 ; Yuan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of adverse events after anti-reflux biliary stent implantation may be as high as 20% ( Hamada et al, 2017 ). In addition, anti-reflux valves such as duckbilled ( Yuan et al, 2019 ), nipple-shaped ( Hu et al, 2014 ), and windsock-shaped valves ( Lee et al, 2016 ) do not significantly improve patient survival. Consequently, ideal anti-reflux biliary stents are still in the stage of design and research.…”
Section: Introductionmentioning
confidence: 99%